PRESPECTIVE OF THEORY OF DIDACTICAL SITUATION TOWARD THE LEARNING OBSTACLE IN LEARNING MATHEMATICS - REFI ELFIRA YULIANI (Sriwijaya University Learning and Education International Conference, 2016)
The learning process of mathematics does not always achieved the expected goals.Various obstacles and difficulties was always coloring process. This is due tovarious factors that become obstacles in the learning process. Diversity intellectualability of students in math vary greatly. The attitude and behavior of students vary,as well as interest and emotions. Methods and designed all aspects of teachers,teaching materials, learning resources, media and classroom situations can help givea boost or provide learning obstacle to the students. The learning obstacles are notonly experienced by students who are capable below average, but can also beexperienced by students at all levels of ability. Brousseau (2002) states that thestudents' thinking evolved from their natural thinking towards logical thinking,which is associated with mathematical reasoning, accompanied by the constructionprocess, the rejection and the use of a method. In the theory of didactical situationsBrousseau was introduced in 1986, the learning obstacles are theoreticalfoundations, because it is a means to acquire knowledge. Obstacles are part of theknowledge of the students in general to solve certain problems, but when faced witha new problem, the knowledge that has been held is not fully used and are difficultto apply it into new material. In other words, the barriers are one way to find outsomething (Brown, 2008). Cognitive obstacles helps to identify the difficulties facedby the students in the learning process, and to determine the right strategy forteaching (Cornu 2002: 158). Brousseau what is proposed in line with Piaget thatknowledge is constructed in the minds of children. Students begin the learningprocess when they are in an environment full of difficulties and obstacles as occursin adults in general. The new knowledge that comes from the ability to adapt to newsituations and stimuli and new reactions to these conditions is evidence that learninghas occurred. Students know that the "problem had to face was deliberately chosento make learning and acquiring new knowledge, knowledge that is justified by thelogic of the situation" (Spagnolo in Manno, 2006). Cornu explained that planning forteaching math concepts is very important to overcome obstacles that may occur.Furthermore, according to artigue (1994), aims to model the situation didacticteaching situations that can be developed with a controlled stages. Thus, in thisdidactic situations students are involved in the process of thinking to solve aproblem in the learning process. This paper describes how the perspective of theorydidactical situation toward the learning obstacle in learning mathematic